Counterproductive effects of anti-CD38 and checkpoint inhibitor for the treatment of NK/T cell lymphoma - Lee, Wendy W. L.; Lim, Jing Quan; Tang, Tiffany P. L.; Tan, Daryl; Koh, Ser Mei; Puan, Kia Joo; Wang, Liang Wei; Lim, Jackwee; Tan, Kim Peng; Chng, Wee Joo; Lim, Soon Thye; Ong, Choon Kiat; et al. (Frontiers in Immunology, 2024)
Natural killer/T cell lymphoma (NKTL) is an aggressive malignancy associated with poor prognosis. This is largely due to limited treatment options, especially for relapsed patients. Immunotherapies like immune checkpoint inhibitors (ICI) and anti-CD38 therapies have shown promising but variable clinical efficacies. Combining these therapies has been suggested to enhance efficacy. We conducted a case study on a relapsed NKTL patient treated sequentially with anti-CD38 followed by ICI (anti-PD1). Cytometry analysis showed an expected depletion of peripheral CD38+ B cells following anti-CD38 treatment. Further analysis indicated that circulating anti-CD38 retained their function for up to 13 weeks post-administration. Anti-PD1 treatment triggered re-activation and upregulation of CD38 on the T cells. Consequently, these anti-PD1-activated T cells were depleted by residual circulating anti-CD38, rendering the ICI treatment ineffective. Finally, a meta-analysis confirmed this counterproductive effect, showing a reduced efficacy in patients undergoing combination therapy. In conclusion, our findings demonstrate that sequential anti-CD38 followed by anti-PD1 therapy leads to a counterproductive outcome in NKTL patients. This suggests that the treatment sequence is antithetic and warrants re-evaluation for optimizing cancer immunotherapy strategies.